Optical architectures for augmented-, virtual-, and mixed-reality headsets - Kress, Bernard C. (SPIE, 2020)
"This book is a timely review of the various optical architectures, display technologies, and building blocks for modern consumer, enterprise, and defense head-mounted displays for various applications, including smart glasses, smart eyewear, and virtual-reality, augmented-reality, and mixed-reality headsets. Special attention is paid to the facets of the human perception system and the need for a human-centric optical design process that allows for the most comfortable headset that does not compromise the user's experience. Major challenges--from wearability and visual comfort to sensory and display immersion--must be overcome to meet market analyst expectations, and the book reviews the most appropriate optical technologies to address such challenges, as well as the latest product implementations"-- Provided by publisher
Keywords: Virtual reality headsets.; Optical instruments -- Design and construction.; Augmented reality -- Equipment and supplies.; elektronické knihy; electronic books